Manajemen Talenta Berbasis Syariah: Pendekatan dan Implementasi di Industri Halal - Nuntupa, Nuntupa; Nugroho, Reza (universitas Islam Zainul Hasan Genggong, 2024)
This paper seeks to provide a new perspective and a new concept in managing sharia-based talent in the halal industry. By using literature study and data analysis, the author hopes to make a meaningful contribution to the development of sharia-based talent Sharia-based Talent Management is an approach that combines modern management principles with Islamic values. In the context of the halal industry, the implementation of sharia-based talent management can help improve company performance through the development of human resources with integrity, fairness, and oriented towards the common good. Thus, the company can get blessings and success in carrying out its business activities.